Kebutuhan Kerja Kolektif dalam Menangani Kasus Kekerasan Seksual di Universitas Indonesia - Putri, Retno Daru Dewi G. S. (Jurnal Perempuan, 2024)
The emergency situation of sexual violence in educational institutions, especially universities, triggered the issuance of Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 on Prevention and Handling of Sexual Violence (Permendikbudristek PPKS). In its implementation, the formation of a Task Force for the Prevention and Handling of Sexual Violence (Satuan Tugas Pencegahan dan Penanganan Kekerasan Seksual – Satgas PPKS) is an obligation for every university in Indonesia. Universitas Indonesia has three organizations that fight for justice for victims of sexual violence by accepting reports and providing assistance and protection: Satgas PPKS UI (PPKS UI Task Force), Komite PPKS FISIP UI (PPKS FISIP UI Committee), and HopeHelps UI. In their work, support from the university is a determinant of success or increasing barriers to combating sexual violence on campus. The experiences of these three organizations are analyzed in this article through Levine’s (2018) three strategies for engaging organizations through Haraway’s (1988) lens of objectivity. The findings in this paper show that the impact of the patriarchal culture and mindset at Universitas Indonesia still marginalizes efforts to implement strategies in fighting for justice for victims of sexual violence.